Linguistic Attenuation in Barranquilla: a Sociopragmatic Study - Torres Fontalvo, Yasmín; Rodríguez Cadena, Yolanda (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article analyzes some of the most frequent attenuating factors used by native Spanish speakers from Barranquilla, while taking into consideration the relation of these factors with social and pragmatic variables such as sex, age, and level of education of the interlocutor. It was a two - stage analysis: the first stage was a qualitative study of the at- tenuating strat egies, markers, pragmatic and semantic functions used by the speakers in their speeches. The second stage was the quantitative phase of research, which developed descriptive and inferential statistics, using the Goldvarb 2001 software. The research sample was taken from the Preseea corpus, which contains 72 informants. The results showed that attenuating factors in Barranquilla vary in accordance with social factors, discursive genres and pragmatic aspects. The use of attenuating factors is also influenced by the type and sex of the interlocutor